2017
DOI: 10.1016/j.exphem.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The Calreticulin control of human stress erythropoiesis is impaired by JAK2V617F in polycythemia vera

Abstract: Calreticulin (CALR) is a Ca2+-binding protein that shuttles among cellular compartments with proteins bound to its N/P domains. The knowledge that activation of the human erythropoietin receptor induces Ca2+ fluxes prompted us to investigate the role of CALR in human erythropoiesis. As shown by Western blot analysis, erythroblasts generated in vitro from normal sources and JAK2V617F polycythemia vera (PV) patients expressed robust levels of CALR. However, Ca2+ regulated CALR conformation only in normal cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 62 publications
7
17
0
Order By: Relevance
“…In mice, CALR exerts nuclear export function of the nuclear receptors, such as the glucocorticoid receptor (GR) which involves migration to the nucleus (Burns et al, 1994 ; Holaska et al, 2001 ). Although, CALR regulates the nuclear export of GR also in human cells, in human cells this activity does not require nuclear localization of CALR but is exerted in regions of the ER located at the nuclear border (Falchi et al, 2017 ), confirming previous studies which had already indicated that nuclear localization of CALR may be an artifact.…”
Section: Biological Functions Of Calrsupporting
confidence: 82%
See 2 more Smart Citations
“…In mice, CALR exerts nuclear export function of the nuclear receptors, such as the glucocorticoid receptor (GR) which involves migration to the nucleus (Burns et al, 1994 ; Holaska et al, 2001 ). Although, CALR regulates the nuclear export of GR also in human cells, in human cells this activity does not require nuclear localization of CALR but is exerted in regions of the ER located at the nuclear border (Falchi et al, 2017 ), confirming previous studies which had already indicated that nuclear localization of CALR may be an artifact.…”
Section: Biological Functions Of Calrsupporting
confidence: 82%
“…In addition, the aforementioned biophysical studies on the urea-induced unfolding of CALR and its isolated domains suggest that also the sensitivity of CALR to urea may be limited by the amount of Ca 2+ bound to the protein, possibly as a reflection of the concentration of this ion in the cells being analyzed. The fact that CALR partially retain its 3D-structure in SDS-PAGE explains why CALR migrates in SDS-PAGE with an apparent molecular weight greater (55–60 KDa) than the theoretical 46 KDa expected on the basis of its AA sequence (Michalak et al, 1992 ; Klampfl et al, 2013 ; Nangalia et al, 2013 ; Falchi et al, 2017 ). Although, it is still unclear whether CALR undergoes post-translational modifications, all the aforementioned post-translational modifications have the potential to affect SDS binding at least to some of its domains allowing CALR to retain some globular structure.…”
Section: Structural Features Of Normal Human Calrmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar association was reported by Mital et al in 142 patients with PV in whom those with VWF:Ag and VWF:Act < 60% and < 50%, respectively, had significantly higher erythrocyte counts. Moreover, PV erythroblasts were found to have increased calreticulin expression on plasma membrane, and calreticulin seems to be involved in the degradation of the circulating VWF/FVIII complex . We also observed a significant association of VWF levels with male sex, not observed in healthy subjects .…”
Section: Discussionmentioning
confidence: 45%
“…So far, the role of CALR mutations in the development of MPN has been only partially elucidated, and no data are available on the physiological function played by CALR during normal hematopoiesis. The only report available is focused on the study of CALR during stress erythropoiesis [12]: the authors demonstrated that in normal proerythroblasts, the CALR C-terminal domain undergoes conformational changes in response to Ca 2+ that activate the nuclear export of the glucocorticoid receptor (GR), resetting the stress response and allowing the cells to undergo terminal differentiation.…”
Section: Introductionmentioning
confidence: 99%